Den undflyende lukten - Jonsson, Kjell; Andersson, Linus (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2018)
This is an overview of the elusive sense of smell, both from a historical/cultural and psychological perspective. We follow two themes. In the first, we describe the repeated efforts to understand and categorize human olfaction, from antiquity to present day. We disseminate how smell has been positioned in sensory hierarchies, describe odor classifications systems and discuss differing views on the relationship between odor and health. The second theme regards how odors and the sense itself has been used as a means for understanding, separating and classifying other phenomena. Odors have throughout history been used to demarcate class boundaries; the (non-)reliance of the sense of smell has been seen as an indication of civilization. Olfactory acuity is used to separate humans from animals, women from men, and young from old. These smell-based taxonomies persist, despite having no clear backing from empirical evidence. Finally, we suggest that the interest in smell may be on the rise, both from a societal and scientific perspective.